Receptor recruitment: A mechanism for interactions between G protein-coupled receptors - Holtbäck, Ulla (The National Academy of Sciences, 1999)
There is a great deal of evidence for synergistic interactions between G protein-coupled signal transduction pathways in various tissues. As two specific examples, the potent effects of the biogenic amines norepinephrine and dopamine on sodium transporters and natriuresis can be modulated by neuropeptide Y and atrial natriuretic peptide, respectively. Here, we report, using a renal epithelial cell line, that both types of modulation involve recruitment of receptors from the interior of the cell to the plasma membrane. The results indicate that recruitment of G protein-coupled receptors may be a ubiquitous mechanism for receptor sensitization and may play a role in the modulation of signal transduction comparable to that of the well established phenomenon of receptor endocytosis and desensitization.